Preparation method of high-performance graphene electromagnetic shielding film

By building a conductive network structure and annealing treatment in graphene electromagnetic shielding materials, the problem of low conductivity of graphene materials is solved, and the preparation of high-performance electromagnetic shielding film is realized, which significantly improves the electromagnetic shielding performance and conductivity, which is suitable for scale Chemical production.

CN119136524APending Publication Date: 2024-12-13GANSU AGRI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411016566.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing electromagnetic shielding materials have problems such as corrosion, low conductivity and poor electromagnetic shielding performance. In particular, the agglomeration of graphene and defects on the six-membered ring lead to their conductivity much lower than the theoretical value, limiting their electromagnetic shielding field. Application.

Method used

By building a conductive network structure, using a high-temperature resistant resin film as a matrix, combining the lattice-intact graphene and modified carbon nanotube powder, the dispersion and intercalation of auxiliary agents prevent the agglomeration of graphene sheets and form highly conductive graphene, forming high-conductive graphene Composite electromagnetic shielding film, printed film formation and annealing treatment are used to obtain high-performance graphene electromagnetic shielding film.

Benefits of technology

It significantly improves the conductivity and electromagnetic shielding performance of graphene films, provides lightweight and high-performance electromagnetic shielding effect, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention belongs to the technical field of electromagnetic shielding materials, and particularly relates to a preparation method of a high-performance graphene electromagnetic shielding film. The method is characterized by comprising the following steps: selecting a high-temperature-resistant resin matrix as a flexible supporting substrate; performing silk-screen printing on graphene composite slurry which is uniformly dispersed, concentrated, evaporated and blended on the high-temperature-resistant flexible support substrate to form a graphene composite film; and annealing the composite film to remove the auxiliary agent and the solvent to obtain the high-performance graphene electromagnetic shielding film. Graphene with complete crystal lattices and modified carbon nano tube powder are adopted as raw materials, a conductive network built by 1D carbon nano tubes and 2D graphene nano tubes is constructed by means of dispersion and intercalation effects of an auxiliary agent, reagglomeration of graphene sheets is hindered, close contact of the conductive material is increased, and the conductivity of the conductive material is improved. And the conductivity and the electromagnetic shielding performance of the silk-screen graphene film are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of film production, and in particular to a method for preparing a high-performance graphene electromagnetic shielding film. Background Art

[0002] The rapid development of communication equipment in the electronic information industry has made the problem of electromagnetic radiation increasingly serious. Electromagnetic radiation refers to the emission or leakage of electromagnetic waves, which interferes with electronic components and harms human health. Especially with the rapid development of 5G communications, a large number of emerging electronic and electrical equipment have emerged, and the dense wiring of chips has caused electromagnetic waves to interfere with each other. While informatization has brought convenience to communication, it has also caused humans to suffer serious harm from electromagnetic radiation. Therefore, the research of high-performance new electromagnetic shielding materials has become an important direction for the development of electromagnetic shielding technology.

[0003] So far, various electromagnetic shielding materials, such as metals (copper, nickel, silver), conductive polymers and inorganic non-metals, have been used to prepare materials with high electromagnetic shielding performance. However, their shortcomings seriously restrict the industrial application of materials. For example, metal-based electromagnetic shielding materials are prone to corrosion; conductive polymers have low conductivity and poor electromagnetic shielding performance. Among the candidate materials in this field, inorganic non-metallic materials have significant advantages such as corrosion resistance, flexibility, light weight and good conductivity. In particular, graphene has good electron mobility (~ 15000 cm 2 •V -1 •s -1 ) and excellent thermal conductivity (~5000 W•m -1 •K -1 ) and is regarded as an electromagnetic shielding material with great development prospects. However, the defects on the agglomerated graphene sheets and the hexacyclic rings make their conductivity far lower than the theoretical value. The present invention improves the conductivity of the graphene film by improving the structural design and assembly method of graphene to produce an oriented and closely connected conductive network. Summary of the invention

[0004] The present invention provides a method for preparing a high-performance graphene electromagnetic shielding film. The graphene electromagnetic shielding material of the present invention enhances the electromagnetic shielding performance by constructing a conductive network structure and a simple annealing treatment, and the prepared lightweight graphene composite electromagnetic shielding film has an excellent electromagnetic shielding effect. The present invention uses a high-temperature resistant resin film as a matrix, and uses graphene with a complete lattice and modified carbon nanotube powder as raw materials. With the help of the dispersion and intercalation effect of auxiliary agents, a conductive network constructed by 1D carbon nanotubes and 2D graphene nanotubes is constructed, which hinders the re-agglomeration of graphene sheets and increases the close contact of conductive materials. A high-performance graphene electromagnetic shielding film is obtained on a high-temperature resistant substrate by means of printing film formation and annealing treatment.

[0005] The high-performance graphene electromagnetic shielding film of the present invention is characterized in that: the graphene film comprises a high-temperature resistant resin matrix and a highly conductive graphene composite slurry screen-printed on the resin matrix. The graphene composite slurry is composed of the following raw materials in mass percentage: 25% to 46.7% graphene, 10% to 20% carbon nanotubes, 15.5% to 30% inorganic metallization compound, 5% to 10% auxiliary agent, and 13.3% to 25% solvent.

[0006] Furthermore, the high temperature resistant matrix refers to one of a polyimide matrix and a silicone resin matrix.

[0007] Furthermore, the graphene refers to powdered graphene nanosheets with a particle size of less than 8 μm and a sheet thickness of less than 3 nm.

[0008] Furthermore, the carbon nanotubes are one or more of amino multi-walled carbon nanotubes, carboxyl carbon nanotubes and hydroxylated carbon nanotubes. The carbon nanotubes have a length ranging from 0.2 to 5 μm, an inner diameter of 5 to 15 nm and an outer diameter of 8 to 30 nm.

[0009] Furthermore, the carbon inorganic metallization compound refers to copper chloride or copper sulfate.

[0010] Furthermore, the auxiliary agent refers to one or more of syringyl lignin, hydroxypropyl methylcellulose, hydroxyethyl cellulose, and sodium carboxymethyl cellulose.

[0011] Furthermore, the solvent refers to one or more of high-purity deionized water, terpineol, n-butanol, tert-butanol, and acetylene glycol.

[0012] The method for preparing the high-performance graphene electromagnetic shielding film as described above comprises the following steps: Step 1: Mix the auxiliary agent, graphene and carbon nanotube powder in deionized water according to a certain mass, stir at 300 rpm for 1 h, then add a vacuum disc stirring device, and continuously stir efficiently for 3 h to prepare a stably dispersed graphene composite solution; Step 2: dissolving a certain amount of an inorganic metal compound in the above graphene composite solution, and subjecting the solution to low-power ultrasound for 10 minutes to uniformly disperse the metal copper ions; Step 3: Evaporate and concentrate the mixed solution to a concentration of 200-220 mg / mL to obtain a high-concentration graphene composite colloid; Step 4: Add alcohol to the above concentrated colloid, stir continuously at 330 rpm for 3 h, adjust the surface tension and viscosity of the graphene colloid, and obtain a high-viscosity, uniformly dispersed graphene printing slurry with a slurry viscosity ranging from 10 Pa•s to 50 Pa•s; Step 5: Using a fully automatic screen printer, screen print the obtained graphene composite slurry on a high temperature resistant flexible substrate, with a printing thickness ranging from 4 to 16 μm; Step 6: Place the graphene film o C / min, heating to 350 o C, annealing in air atmosphere for 50 min to promote carbonization of the auxiliary agent and volatilization of the solvent, and finally obtain a high-performance graphene electromagnetic shielding film; Advantages and beneficial effects of the present invention: 1. The present invention uses a flexible high temperature resistant resin as a printing substrate, prepares a graphene composite slurry with excellent printing performance, and uses screen printing combined with one-step annealing to obtain a high-performance electromagnetic shielding graphene film. This method is a feasible method for preparing high-performance graphene electromagnetic shielding films that can be mass-produced; 2. The present invention utilizes the intercalation and dispersion effect of auxiliary agents on graphene and carbon nanotubes to construct a conductive network structure that is beneficial to the enrichment of metal copper ions on graphene nanosheets. Combined with the stacking inhibition effect of carbon nanotubes on graphene and the increase in carrier density by copper ion doping, the electrical conductivity of graphene is effectively improved to obtain a high-performance graphene electromagnetic shielding film. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The electromagnetic shielding performance of the graphene film is obtained through Example 1 of the present invention. DETAILED DESCRIPTION

[0014] Example 1 A high-performance graphene electromagnetic shielding film, the graphene film comprising a high-temperature resistant polyimide matrix and a prepared highly conductive graphene composite slurry. The graphene composite slurry is composed of the following raw materials in percentage by mass: 46.7% graphene, 13.3% amino multi-walled carbon nanotubes, 15.5% metallized anhydrous copper chloride, 6.7% auxiliary agent syringyl lignin, and 17.8% solvent mixture of deionized water and pine alcohol The method for preparing the high-performance graphene electromagnetic shielding film comprises the following steps: Step 1: Mix syringyl lignin, graphene and amino multi-walled carbon nanotube powder in 2 L of deionized water at a mass ratio of 1:7:2, stir at 300 rpm for 1 h, then add a vacuum disc stirring device and continuously stir efficiently for 3 h to prepare a stably dispersed graphene composite solution; Step 2: Add a certain mass of anhydrous copper chloride to the above graphene composite solution in a mass ratio of 1:3 to the graphene in step 1, and perform low-power ultrasound for 10 min; Step 3: Evaporate and concentrate the mixed solution to a solid concentration of 200-220 mg / mL to obtain a high-concentration graphene composite colloid; Step 4: Add pinene alcohol to the above concentrated colloid, stir continuously at 330 rpm for 3 h, adjust the surface tension and viscosity of the graphene colloid, and obtain a high-viscosity, uniformly dispersed graphene printing slurry with a slurry viscosity of 12 Pa•s; Step 5: With the aid of a fully automatic screen printer, the obtained graphene composite slurry is screen-printed on a high temperature resistant flexible substrate with a printing thickness of 15.7 μm; Step 6: Place the graphene film o C / min rate of heating 350 o C, annealed in air atmosphere for 50 min, and then cooled to room temperature to obtain a high-performance graphene electromagnetic shielding film.

[0015] Example 2 A high-performance graphene electromagnetic shielding film, the graphene film comprising a high temperature resistant silicone resin matrix and a formulated high-conductivity graphene composite slurry. The graphene composite slurry is composed of the following raw materials in percentage by mass: 30% graphene, 10% hydroxylated carbon nanotubes, 30% anhydrous copper sulfate of a metal compound, 10% auxiliary agent hydroxypropyl methylcellulose, and 20% solvent mixture of deionized water and n-butanol.

[0016] The method for preparing the high-performance graphene electromagnetic shielding film comprises the following steps: Step 1: Mix hydroxypropyl methylcellulose, graphene and hydroxylated carbon nanotube powder in 2 L of deionized water at a mass ratio of 1:3:1, stir at 300 rpm for 1 h, then add a vacuum disc stirring device and continue to stir efficiently for 3 h to prepare a stably dispersed graphene composite solution.

[0017] Step 2: Add a certain mass of anhydrous copper sulfate to the above graphene composite solution in a mass ratio of 1:1 to the graphene in step 1, and perform low-power ultrasound for 10 minutes.

[0018] Step 3: Evaporate and concentrate the mixed solution to a concentration of 200-220 mg / mL to obtain a high-concentration graphene composite colloid.

[0019] Step 4: Add tert-butanol to the above concentrated colloid, stir continuously at 330 rpm for 3 h, adjust the surface tension and viscosity of the graphene colloid, and obtain a high-viscosity, uniformly dispersed graphene printing slurry with a slurry viscosity of 16.9 Pa•s.

[0020] Step 5: With the help of a fully automatic screen printing machine, the obtained graphene composite slurry is screen-printed on a high temperature resistant flexible substrate with a printing thickness of 16.3 μm.

[0021] Step 6: Place the graphene film o C / min rate of heating 350 oC, annealed in air atmosphere for 50 min, and then cooled to room temperature to obtain a high-performance graphene electromagnetic shielding film.

[0022] Embodiment 3 A high-performance graphene electromagnetic shielding film, the graphene film comprising a high temperature resistant silicone resin matrix and a prepared highly conductive graphene composite slurry. The graphene composite slurry is composed of the following raw materials in percentage by mass: 25% graphene, 20% hydroxylated carbon nanotubes, 25% anhydrous copper sulfate of a metalized compound, 5% auxiliary agent hydroxyethyl cellulose, and 25% of a mixture of deionized water and n-butanol as a solvent.

[0023] The method for preparing the high-performance graphene electromagnetic shielding film comprises the following steps: Step 1: Mix hydroxyethyl cellulose, graphene and hydroxylated carbon nanotube powder in 2 L of deionized water at a mass ratio of 1:5:4, stir at 300 rpm for 1 h, then add a vacuum disc stirring device and continue to stir efficiently for 3 h to prepare a stably dispersed graphene composite solution.

[0024] Step 2: Add a certain mass of anhydrous copper sulfate to the graphene composite solution in a mass ratio of 1:1 to the graphene in step 1, and perform low-power ultrasound for 10 min.

[0025] Step 3: Evaporate and concentrate the mixed solution to a concentration of 200-220 mg / mL to obtain a high-concentration graphene composite colloid.

[0026] Step 4: Add acetylene glycol to the above concentrated colloid, stir continuously at 330 rpm for 3 h, adjust the surface tension and viscosity of the graphene colloid, and obtain a high-viscosity, uniformly dispersed graphene printing slurry with a slurry viscosity of 16.9 Pa•s.

[0027] Step 5: With the help of a fully automatic screen printing machine, the obtained graphene composite slurry is screen-printed on a high temperature resistant flexible substrate with a printing thickness of 16.0 μm.

[0028] Step 6: Place the graphene film o C / min rate of heating 350 o C, annealed in air atmosphere for 50 min, and then cooled to room temperature to obtain a high-performance graphene electromagnetic shielding film.

[0029] Comparative Example 1 A graphene electromagnetic shielding film, comprising a high temperature resistant silicone resin matrix and a prepared highly conductive graphene composite slurry, wherein the graphene composite slurry is composed of the following raw materials in percentage by mass: 45% graphene, 25% anhydrous copper sulfate of a metallized compound, 5% auxiliary agent hydroxypropyl methylcellulose, and 25% of a mixture of deionized water and n-butanol as a solvent.

[0030] The method for preparing the graphene electromagnetic shielding film comprises the following steps: Step 1: Mix hydroxypropyl methylcellulose, graphene and hydroxylated carbon nanotube powder in 2L deionized water at a mass ratio of 1:9, stir at 300 rpm for 1 h, then add a vacuum disc stirring device and continue to stir efficiently for 3 h to prepare a stably dispersed graphene composite solution.

[0031] Step 2: Add a certain mass of anhydrous copper sulfate to the graphene composite solution in a mass ratio of 1:1.8 to the graphene in step 1, and perform low-power ultrasound for 10 min.

[0032] Step 3: Evaporate and concentrate the mixed solution to a concentration of 200-220 mg / mL to obtain a high-concentration graphene composite colloid.

[0033] Step 4: Add tert-butanol to the above concentrated colloid and stir continuously at 330 rpm for 3 h to adjust the surface tension and viscosity of the graphene colloid to obtain a high-viscosity, uniformly dispersed graphene printing slurry with a slurry viscosity of 17.4 Pa•s.

[0034] Step 5: With the help of a fully automatic screen printing machine, the obtained graphene composite slurry is screen-printed on a high temperature resistant flexible substrate with a printing thickness of 15.8 μm.

[0035] Step 5: Place the graphene film o C / min rate of heating 350 o C, annealed in air atmosphere for 50 min, and then cooled to room temperature to obtain a graphene electromagnetic shielding film.

[0036] The conductivity and electromagnetic shielding performance of the graphene electromagnetic shielding films prepared in Examples 1 to 3 and Comparative Example 1 were tested respectively, and the results are shown in Table 1: Table 1 Film thickness (μm) Conductivity (S / cm) Electromagnetic shielding effectiveness (dB) Example 1 15.7 832.4 29.4 Example 2 16.0 736.5 30.1 Example 3 16.0 736.5 30.1 Comparative Example 1 16.3 683.4 23.7 According to Examples 1 to 3 in Table 1, the conductive network structure constructed by carbon nanotubes and graphene nanosheets constructed in the present invention significantly improves the conductivity and electromagnetic shielding performance of the film. In Comparative Example 1, the electromagnetic shielding performance of the graphene film constructed solely by graphene nanosheets without the addition of carbon nanotubes is poor.

[0037] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A high-performance graphene electromagnetic shielding film, characterized in that: The graphene film includes a high temperature resistant resin substrate and a highly conductive graphene composite slurry that can be screen printed. The graphene composite slurry is composed of the following raw materials in percentage by mass: 25% to 46.7% graphene, 10% to 20% carbon nanotubes, 15.5% to 30% inorganic metallization compound, 5% to 10% auxiliary agent, and 13.3% to 25% solvent.

2. The high performance graphene electromagnetic shielding film according to claim 1, characterized in that: The high temperature resistant matrix is ​​one of a polyimide matrix and a silicone resin matrix.

3. The high-performance graphene electromagnetic shielding film according to claim 1, characterized in that: The graphene refers to powdered graphene nanosheets with a particle size of less than 8 μm and a sheet thickness of less than 3 nm.

4. The high-performance graphene electromagnetic shielding film according to claim 1, characterized in that: The carbon nanotubes are one or more of amino multi-walled carbon nanotubes, carboxyl carbon nanotubes and hydroxylated carbon nanotubes. The carbon nanotubes have a length ranging from 0.2 to 5 μm, an inner diameter of 5 to 15 nm and an outer diameter of 8 to 30 nm.

5. The high-performance graphene electromagnetic shielding film according to claim 1, characterized in that: The carbon inorganic metallization compound refers to copper chloride and copper sulfate.

6. The high-performance graphene electromagnetic shielding film according to claim 1, characterized in that: The auxiliary agent refers to one or more of syringyl lignin, hydroxypropyl methylcellulose, hydroxyethyl cellulose and sodium carboxymethyl cellulose.

7. The high-performance graphene electromagnetic shielding film according to claim 1, characterized in that: The solvent refers to one or more of high-purity deionized water, terpineol, n-butanol, tert-butanol, and acetylene glycol.

8. The method for preparing a high-performance graphene electromagnetic shielding film according to claim 1, characterized in that: The following steps are involved: Step 1: The auxiliary agent, graphene and carbon nanotube powders are mixed in deionized water according to a certain mass, stirred at 300 rpm for 1 h, and then added to a vacuum disc stirring device, and continuously stirred efficiently for 3 h to prepare a stably dispersed graphene composite solution; Step 2: dissolving a certain amount of an inorganic metal compound in the above graphene composite solution, and subjecting the solution to low-power ultrasound for 10 minutes to uniformly disperse the metal copper ions; Step 3: Evaporate and concentrate the mixed solution to a concentration of 200-220 mg / mL to obtain a high-concentration graphene composite colloid; Step 4: Add alcohol to the above concentrated colloid, stir continuously at 330 rpm for 3 h, adjust the surface tension and viscosity of the graphene colloid, and obtain a high-viscosity, uniformly dispersed graphene printing slurry with a slurry viscosity ranging from 10 Pa•s to 50 Pa•s; Step 5: Using a fully automatic screen printer, screen print the obtained graphene composite slurry on a high temperature resistant flexible substrate, with a printing thickness ranging from 4 to 16 μm; Step 6: Place the graphene film o C / min, heating to 350 o C, annealing in air atmosphere for 50 min to promote carbonization of the auxiliary agent and volatilization of the solvent, and finally obtain a high-performance graphene electromagnetic shielding film.

Citation Information

Cited By

  • Preparation method of high-stability graphene slurry

    CN120483128A